Management of Recurrent Cholangitis in Patient with Iatrogenic Bile Duct Stricture - Tessa Oktaramdani; Ari Fahrial Syam; Dadang Makmun (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2015)
Iatrogenic bile duct stricture is the most common causes of benign bile duct stricture. Several studies reported that approximately 80% of benign strictures occur following injury during a cholecystectomy. Strictures of the biliary tract have a broad spectrum of manifestations, ranging from mild elevation of liver enzymes to life-threatening infections such as cholangitis, liver abscess, and biliary cirrhosis. Moreover, due to its indolent course with subtle clinical manifestations, diagnosis is often delayed and most patients present with a protracted, complicated course. We reported a case of 26 years old female with recurrent cholangitis due to iatrogenic bile duct stricture. Biliary drainage through endoscopic approach followed by surgical procedure was selected as strategic management for the patient.